A midsummer night's dream : with connections - Shakespeare, William, 1564-1616 (New York : Holt, Rinehart, and Winston, 2000)
Drama.
Keywords: Courtship -- Drama; Athens (Greece) -- Drama; Hippolyta (Greek mythology) -- Drama